STUDI KOMPARASI PEMBUATAN PAKAN IKAN DENGAN MODEL CANVAS - Sheli Oktavia (Universitas Pamulang, 2021)
One of the main obstacles in fish farming is the problem of feed. Feed sucks up to 70% of the production cost of fish farming. The purpose of this study was to identify the business model in the Mina Perkasa Cangkring Group and the Mujaer Lele Nila Group with the Business Model Canvas approach; create a business model that has been perfected in the Mina Perkasa Cangkring Group and the Mujaer Lele Nila Group, with the Business Model Canvas approach and create improvement programs that can be made from the enhanced business model. The results of the research on identification of customer segments from the Mina Perkasa Cangkring group were vaname shrimp cultivators in the Mina perkasa Cangkring group, vaname shrimp cultivators in Cantigi and Losarang sub-districts. Meanwhile, the Mujaer Lele Nila group was catfish cultivators in the Nila Lele Mujaer Group. Identification of value proposition elements The Mina Perkasa Cangkring group is located in the cultivation area, the quality of the feed offered is relatively good and the price is cheap. Meanwhile, the Mujaer Lele Nila group is only cheap. The identification of customer relationship elements from the Mina Perkasa Cangkring group is a discount for group members and commissions for customers who selling feed. Meanwhile, the Mujaer Lele Nila Group does not take any profit from selling feed to fellow members. Identification of channel elements in the Mina Perkasa Cangkring Group is to use network facilities among shrimp farmers in Cantigi District. Meanwhile, the channel of the mujaer catfish tilapia group uses group members and extension workers. The results of the identification of key activities elements of the Mina Perkasa Cangkring Group are semi-intensive vaname shrimp cultivation and feed production. Meanwhile, the Mujaer Lele Nila group is catfish cultivation and feed manufacture. The results of the identification of key resource elements in the Mina Perkasa Cangkring and Mujaer Lele Nila groups are mini feed factories, warehouses, printing machines, flour machines, mixing machines, raw materials and human resources. Identification of key partnership elements from the Mina Perkasa Cangkring Group and Mujaer Lele Nila, who are providers of raw materials and extension workers. The results of the identification of revenue stream elements in the Mina Perkasa Cangkring and Mujaer Lele Nila groups are the results of the sale of feed. The results of the identification of cost structure elements in the Mina Perkasa Cangkring Group are equipment maintenance, purchase of raw materials, employee salaries, packaging costs and promotion costs. Meanwhile, the cost structure for the Mujaer Lele Nila Group is equipment maintenance, purchase of raw materials and employee salaries.Keywords: Fish Feed Business, Canvas Model